PELATIHAN PERAKITAN DAN INSTALASI KOMPUTER UNTUK SANTRIWAN/SANTRIWATI DI DAYAH TERPADU SYAMSUDDHUHA ACEH UTARA - Zara Yunizar Zainal; Bustami Bustami; Lidya Rosnita; Rini Meiyanti; Fasdarsyah Fasdarsyah (LPPM Universitas Al Muslim, 2022)
Along with development of globalization era, world of Information and Communication Technology is also growing rapidly and it has become a primary need for many people, including students. By applying information and Communication Technology, a process and activity can be carried out more quickly, easily and efficiently. Therefore, mastery of communication technology devices needs to be taught to students in Islamic boarding schools or dayah. Community service is an effort of Malikussaleh University to contribute in science and technology to the students. Purpose of the service is to provide training on computer assembly and installation to Santriwan/Santriwati at Syamsuddhuha Integrated Dayah. This training is expected to provide students with provisions regarding computer assembly and installation. Outcomes of this activity are: (1) The student is able to know each function of computer assembling and installing, and (2) participants have the ability to understand computer and its components.